Rethinking World System Theory: A Historical and Conceptual Analysis - Burhanuddin, Agussalim (WANUA : Jurnal Hubungan Internasional, 2015)
This article is a historical and conceptual analysis of World Systems Theory which proposed by Immanuel Wallerstein. This paper aims to explore historical framework of world system theory, explain the unit of analysis, and describe its relationship with other social science theories. Historical exploration of Wallerstein and this theory show a strong influence of historical study were obtained from Wallerstein background and people around him. Conceptual analysis to this theory shows that Wallerstein use Marxâs concept about social class struggle then raise in a global context by using state as the actors. In conjunction with other theories, world system theory fundamentally supports theory of dependence from Gunder Frank, and otherwise sharply criticizes modernization approach and developmental stage model by Walt Rostow.